2002
DOI: 10.1101/gad.218702
|View full text |Cite
|
Sign up to set email alerts
|

Pseudosubstrate regulation of the SCFβ-TrCP ubiquitin ligase by hnRNP-U

Abstract: ␤-TrCP/E3RS (E3RS) is the F-box protein that functions as the receptor subunit of the SCF␤-TrCP ubiquitin ligase (E3). Surprisingly, although its two recognized substrates, IB␣ and ␤-catenin, are present in the cytoplasm, we have found that E3RS is located predominantly in the nucleus. Here we report the isolation of the major E3RS-associated protein, hnRNP-U, an abundant nuclear phosphoprotein. This protein occupies E3RS in a specific and stoichiometric manner, stabilizes the E3 component, and is likely respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 57 publications
10
100
0
Order By: Relevance
“…SFB might function as a component of SCF SFB and ubiquitinate all of the nonself S-RNases for degradation but interact specifically with the self S-RNase to leave it active, leading to the arrest of self pollen tube growth. Recently, it was reported that hnRNP-U functions as a pseudosubstrate that binds to the corresponding F-box protein but is not destined for degradation by the SCF complex (Davis et al, 2002). Based on this example, it is possible that self S-RNase serves as a pseudosubstrate for Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…SFB might function as a component of SCF SFB and ubiquitinate all of the nonself S-RNases for degradation but interact specifically with the self S-RNase to leave it active, leading to the arrest of self pollen tube growth. Recently, it was reported that hnRNP-U functions as a pseudosubstrate that binds to the corresponding F-box protein but is not destined for degradation by the SCF complex (Davis et al, 2002). Based on this example, it is possible that self S-RNase serves as a pseudosubstrate for Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that some critical factors mediating constitutive p100 processing are located in the nucleus. For example, a number of ubiquitin ligases, including SCF βTrCP , are predominantly localized in the nucleus [27][28][29][30][31]. Although SCF βTrCP is dispensable for constitutive processing of p100 [15], the possibility for the involvement of another nuclear ubiquitin ligase(s) in this molecular event cannot be excluded.…”
Section: Suppression Of Constitutive Processingmentioning
confidence: 99%
“…Because a similar motif is found within the cytoplasmic C-terminal domain of LMP1-95-9 (Fig. 1C), we chose to focus our studies on interaction of LMP1 with HOS, which, unlike ␤-TrCP1, is primarily localized in the cytoplasm (49,50).…”
Section: Lmp1-95-8 But Not Lmp1-cao Interacts With Hos-mentioning
confidence: 99%